Toxicity effects of an insecticidal soap on the green peach aphid [Homoptera: Aphididae] - Tremblay, Éléonore; Bélanger, André; Brosseau, Marcel; Boivin, Guy (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2009)
Effects of an insecticidal soap on the survival, development and reproduction of the green peach aphid, Myzus persicae, were studied. Twenty-four hours after application at a concentration of 37.50 g L-1, the soap caused 100% mortality in all aphid instars, and LC50 (lethal concentrations causing 50% mortality in the population) were 1.50, 3.25 and 5.50 g L-1 for first and second instars, third and fourth instars, and adult M. persicae, respectively. Aphids that survived the LC50 had a shorter longevity than the controls. Both insecticidal soap and parasitoids could be used on a crop but, as the LC50 of the third and fourth instars and adult M. persicae are higher than that of the aphid parasitoid Aphidius colemani (2.75 g L-1), it is essential to avoid treating aphids with insecticidal soap when adult parasitoids are present in the crop.